Experimental Study and Numerical Simulation of Sheet Hydroforming Process for Aluminum Alloy AA5652 - Sadoon, Muthanna Hamza; Aziz, Sadiq Jaffar; Jassim, Hiba AbdAli (Al-Khwarizmi Engineering Journal, 2015)
Abstract   Lightweight materials is used in the sheet metal hydroforming process,  because it can be adapted to the manufacturing of complex structural components into a single body with high structural stiffness. Sheet hydroforming has been successfully developed in industry such as in the manufacturing of the components of automotive.The aim of this study is to simulate the experimental results ( such as the amount of pressure required to hydroforming process, stresses, and strains distribution)  with results  of finite element analyses (FEA)  (ANSYS 11)  for aluminum alloy (AA5652) sheets with  thickness (1.2mm) before heat treatment (BHT) and after heat treatment (AHT) respectively in the circular die with cavity equals to (20mm) . The comparison of results by these two approaches show the same tendency that an improvement formability, also  the plastic deformation is greatly enhanced AHT for same metal. Keyword : sheet hydroforming , stress and strain distribution, aluminum alloy, forming limit diagram.